Arduino Based Design of Horizontal Wind Power Generator for Coastal Road Lighting - Rochman, Sagita; Taufiq Irvan Efendy, Mochamad (BEST, 2021)
Increasing energy demand, depleting fossil fuel reserves, and environmental concerns have put renewable energy sources in the spotlight in Indonesia. Wind energy in particular, which has received a lot of attention because it is inexhaustible and friendly to the environment. The main problem of the two generating systems is not continuously available. Wind turbines are the main medium used to convert wind energy into electrical energy. A good wind turbine design will determine the performance of a wind power plant (PLTB). This tool is to control the electric power generated from the wind generator, the electric power generated from the generator will be measured the current and voltage. The way the tool works when the generator wheel rotates, the generator will produce electrical power which has been connected to the charger controller before the electric power is stored in the battery. The use of electric power from the battery will be converted using an inverter to convert the DC current to AC. This research was conducted on wind turbine generators in the use of coastal street lighting as objects to generate electric power in order to reduce the need for PLN electricity. This research was conducted on wind turbine generators in the use of coastal street lighting as objects to generate electric power in order to reduce the need for PLN electricity. The generator will generate electrical power which has been connected to the charger controller before the electric power is stored in the battery. The use of electric power from the battery will be converted using an inverter to convert the DC current to AC. This research was conducted on wind turbine generators in the use of coastal street lighting as objects to generate electric power in order to reduce the need for PLN electricity